Guided Imagery Relaxation Effectively Lowers Blood Pressure in Hypertension Patients - Kayubi Kayubi; Hasim Asyari; Indra Ruswadi (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Hypertension is a leading risk factor for cardiovascular diseases and is prevalent in various age groups. Effective interventions are needed to manage hypertension, particularly in primary healthcare settings. This study explores the effect of guided imagery relaxation on reducing blood pressure in hypertensive patients at Puskesmas Babadan, Indramayu. Objectives: This study aimed to determine the effectiveness of guided imagery relaxation in lowering systolic and diastolic blood pressure in hypertensive patients. Methods: A pre-experimental design was used involving 30 hypertensive patients from Puskesmas Babadan. Participants underwent a guided imagery relaxation intervention for 15 minutes daily over one week. Blood pressure was measured before and after the intervention. Data were analyzed using paired t-tests to assess changes in blood pressure. Results: The results showed a significant reduction in both systolic and diastolic blood pressure after the intervention. The mean systolic blood pressure decreased from 152.3 mmHg to 140.5 mmHg (p = 0.000), while diastolic blood pressure decreased from 94.6 mmHg to 88.1 mmHg (p = 0.001). Conclusions: Guided imagery relaxation was effective in lowering blood pressure in hypertensive patients. This non-pharmacological approach may be a valuable complementary therapy in managing hypertension in primary healthcare settings. Further research is recommended to explore the long-term effects and the integration of this technique into routine healthcare practices.